Ablation behavior of inorganic particle-filled polybenzoxazine composite coating irradiated by high-intensity continuous laser. Issue 12 (15th August 2019) - Xu, Feng; Zhu, Shizhen; Ma, Zhuang; Li, Hezhang; Wang, Jiawei; Wu, Taotao; Wang, Fuchi
Abstract: Further utilization of aircraft structural materials is threatened by the fact that high-intensity continuous lasers are widely used in the field of military defense. To protect the aircraft structure from laser damage, ammonium polyphosphate filled polybenzoxazine composite coatings were prepared on the substrate. The anti-laser ablation characteristics of the coatings were investigated. Results showed that the addition of the inorganic filler improved the anti-laser ablation performance of polybenzoxazine. The back-surface temperature of substrates covered with the composite coatings was more 50% lower than that in the case of a pure polybenzoxazine coating after laser ablation. Further, the residue of the composite coating could be vertically divided into three distinct regions, with the dense surface char layer and the porous pyrolysis layer acting as shielding layers for the laser beam and preventing any heat-related transformations from occurring. The addition of the inorganic particles improved the surface reflectivity of the coatings resulting in much more laser energy dissipation. The decreased pyrolysis rate ensured that the pneumatic cooling effect of pyrolysis gas was more lasting and stable, owing to which the composite coatings could act as effective thermal protection layer for longer. These results confirmed that the inorganic filler modified polybenzoxazine coating exhibits excellent anti-laser properties and are suitable for protecting structural materials from laser-related damage.